17.5: Fabrication of CdSe/ZnS Quantum Dot Color Filters via Photolithography Process. (28th November 2018) - Zhao, Bingxin; Lu, Rui; Hao, Junjie; Li, Shang; Bai, Xue; Wang, Liduo; Wang, Kai; Sun, Xiao Wei
Abstract : Quantum dots color filter (QDCF) is potential to be a game‐changer for display and micro LED industry. In this paper, highly fluorescent QDCF have been prepared by changing surface active ligand of CdSe@ZnS to nonreactive ligand for photolithographic patterning. The quantum dots (QDs) with inactivated ligand avoids chemical reaction during the photolithography process. The 4 μm thickness QDCF with 28.8% (red) absolute PL quantum yield (λmax of 630.16 nm) has been achieved after the photolithograpy process, while the QDs with surface active sites failed to form a patterned film. This may be due to the coordination of activated bonds with photoresist and the occurrence of complexation reaction.